Dramaturgy in Digital Public Accounting: Social Representation and Institutional Imaging in the Era of Digital Transformation - Dian Fathirah; Dea Saufika Mobilingo; Alimuddin Alimuddin (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
Accounting practices in public institutions are no longer merely financial reporting tools, but also strategic instruments for building institutional image, particularly through digital platforms. This research adopts Erving Goffman's dramaturgy approach to analyze how actors in public institutions manage impressions through financial report presentations and institutional communication activities connected to digital systems, including social media and e-reporting. The concepts of front stage and back stage are used to understand the disparity between formal representations displayed digitally to the public and the internal organizational reality. Findings reveal the use of digital systems as part of social performance to create an image of transparency, which often does not reflect actual operational conditions. This research highlights new challenges in maintaining accountability and public trust in the era of digital transformation. Thus, the dramaturgy approach provides a critical perspective in understanding the social and technological dynamics behind digital public sector accounting practices.